Production and management of Energy; the interdisciplinary approach of ENEA to Concentrated Solar Power - Domenico De Martinis; Alberto Giaconia (Renewable Energy and Sustainable Development)
Clean and efficient energy generation by environmental friendly methods and technologies is now one of the major challenges worldwide. New and heterogeneous methods to produce energy pose the challenge of how to guarantee energy security, storage of exceeding production and distribution. In addition to that, the exploitation of next generation energy sources must consider the impact it may have on other productive systems and on rural areas (e.g. solar vs agriculture, biomass vs food production). ENEA has got and follows an interdisciplinary approach to “challenge the challenge” of a sustainable energy production, merging together materials science, agronomy and biotechnology, solar energy studies, energy efficiency management and more, in collaboration with industries and often in collaboration with the other stakeholders in the Mediterranean area.  This paper describes the state of the art technology and how concentrating solar power (CSP) technology could be modulated to meet different energy needs, both spatial needs (e.g.  off grid use vs dispatchability) and temporal needs (day vs night and energy on demand).